Bula de software representada por mapas conceituais - Martinez, Patrícia Valério (2018)
This dissertation presents a proposal for a package insert for software, which allows to capture information related to the characteristics and functionalities of a certain software, following a predefined structure. The theoretical basis of the work is composed of theories of conceptual maps and the drug package. The software package, represented through conceptual maps, can produce an understanding of software product functionality. Complemented by an experimental research, this work verifies the efficiency of the software package in the transmission of knowledge, through an experiment involving 73 participants. It results in a template for software that can be used by the industry with the objective of raising one of the characteristics that is the understanding.